Condiçoes higiênico-sanitárias da água e do camarão em duas fazendas de cultivo de pequeno e médio portes, no Estado do Ceará - Parente, Lucélia Saboia (2005)
The shrimp species Litopanaeus vannamei is the single most important aquiculture resource in Northeastern Brazil. However, the rapid expansion of the activity has brought with it a number of water and food-borne bacterial diseases. The objective of the present study was to evaluate and compare the sanitary conditions of shrimp and pond water sampled at one small and one medium-sized shrimp farm in Ceará State. Thus, Escherichia coli was quantified by determining the most probable number (MPN) of fecal coliforms (FC) and total coliforms (TC) in a total of 41 water and 37 shrimp samples collected from two ponds at each farm between March and October 2004 and tested for Salmonella. FC and TC levels were roughly the same in water from the two farms, but shrimp collected from the smaller farm were more severely contaminated. Considering all four ponds investigated, 65% of the 80 strains isolated from water samples and 58.1% of the 124 strains isolated from shrimp samples could be identified as E. coli, while Salmonella was detected in two water samples and one shrimp sample. Since these pathogens are of fecal origin and inhabit the intestines of warm-blooded animals, their presence in local shrimp culture is of great relevance to public health and should be carefully monitored by the authorities to prevent contamination through human consumption.